2014
DOI: 10.3354/aei00098
|View full text |Cite
|
Sign up to set email alerts
|

Vertical salmon lice behaviour as a response to environmental conditions and its influence on regional dispersion in a fjord system

Abstract: The salmon louse Lepeophtheirus salmonis is a major parasite of salmon, and is able to travel between farms during its pelagic phases. We investigated the spatial dispersion of L. salmonis planktonic stages in the Hardangerfjord, Norway, using an individual-based model and a fjord circulation model. The models allowed us to investigate how assumptions about swimming responses to environmental cues affect vertical distribution, development and horizontal transport. The rules governing vertical distributions inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 44 publications
2
88
0
Order By: Relevance
“…Such variations that cannot be fully predicted are common in many ecological studies and although not all relevant details may ever be available, it would likely have been possible to reduce the noise and improve the models by having a more thorough sampling design and higher number of data points. Further, recent approaches of spatiotemporal models of salinity, temperature and currents in the fjords may improve the availability of relevant environmental data (Asplin et al 2011, Salama & Rabe 2013, Johnsen et al 2014. Although statistical models based on rather coarse-scale proxy data can be used to identify factors influencing the infection pressure on wild salmonids, as we have tried here, this approach may not be that useful for determining whether individual areas have a lice problem owing to finer-scale environmental variation.…”
Section: Discussionmentioning
confidence: 97%
“…Such variations that cannot be fully predicted are common in many ecological studies and although not all relevant details may ever be available, it would likely have been possible to reduce the noise and improve the models by having a more thorough sampling design and higher number of data points. Further, recent approaches of spatiotemporal models of salinity, temperature and currents in the fjords may improve the availability of relevant environmental data (Asplin et al 2011, Salama & Rabe 2013, Johnsen et al 2014. Although statistical models based on rather coarse-scale proxy data can be used to identify factors influencing the infection pressure on wild salmonids, as we have tried here, this approach may not be that useful for determining whether individual areas have a lice problem owing to finer-scale environmental variation.…”
Section: Discussionmentioning
confidence: 97%
“…A degree-day is the product of time and temperature (e.g., 30 days at 10°C = 300 degree-days), and it is a useful index of "physiological age" or the temperature required for growth and development of ectotherms within their range of tolerance (Costello 2006). Moreover, this index is used as a temperature-dependent development time in salmon lice dispersal models Johnsen et al 2014). Here, we calculated degree-days by multiplying the mean temperature of the incubators by development time in days.…”
Section: Development Times Of Salmon Lice Planktonic Larval Stagesmentioning
confidence: 99%
“…To test for differences in distribution patterns due to variations in development times to the infective stage, we used simulations from an individual-based coupled biological-physical dispersal model (described in Johnsen et al (2014). In our simulation, 10 particles, representing salmon lice during its planktonic stages, were released every hour from two sites (coastal and fjord site) around the Hardangerfjord area (60°N, 5.5°E) on the west coast of Norway for a winter month in January 2015.…”
Section: Simulated Salmon Lice Dispersal Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gillibrand & Willis (2007) and Johnsen et al (2014) showed that relatively small vertical movement behaviors had a significant effect on the dis persion pattern in stratified waters, emphasizing the need for a more comprehensive model in estuarine-driven areas. However, outside the Faroese fjords, where the circulation is dominated by the tides (Larsen et al 2008), the connectivity between the salmon farming locations will those also be dominated by tides.…”
Section: Biological Parametersmentioning
confidence: 99%